2D Ising Model With Point Defect at Adjacent Sites - Kanwar, Sagar; Lamichhane, Sudeep; Dhami, Pankaj Singh; Adhikari, Narayan Prasad (Journal of Nepal Physical Society, 2024)
The study examines the magnetization behaviour in a 2D Ising model with single and double point defects using Monte Carlo simulations. At elevated tempera- tures, thermal fluctuations dominate, leading to a disordered state with negligible magnetic moment. As temperature decreases, defects influence spin alignment. At very low temperatures, the magnetization due to single-point defects is minimal, whereas two-point defects significantly alter magnetization. This occurs due to local perturbations in spin alignment, leading to disruptions in nearby spins and reducing overall magnetization. Additionally, thermal fluctuations play a crucial role in the behavior of the Ising model at finite temperatures. Point defects can increase thermal fluctuations around the defect sites, further contributing to the reduction in overall magnetization. The findings presented in this research con- tribute to a better understanding of the role of defects in magnetic systems, with potential applications in material science. Further investigations using larger lat- tice sizes and higher defect concentrations could provide more insights in optimizing magnetic properties in real-world systems.